2004
DOI: 10.1039/b314264g
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-assisted antibody catalysis

Abstract: A new strategy in transition-state analog design is demonstrated to elicit catalytic antibodies. The strategy is based on substrate-assisted antibody catalysis and utilizes analogs designed to mimic the transition-state for intramolecular catalysis and thereby favor antibodies that can recruit catalytic groups from substrate. The hydrolysis of the benzoyl ester of cocaine provides an illustration. The benzoyl ester of cocaine is distant from the protonated nitrogen in the stable chair conformer but proximate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Such a TSA structure (depicted in Chart ) was synthesized and 85 cocaine esterases out of 450 antianalog antibodies were elicited—a performance markedly superior to that of a previously employed simple phosphonate ester as a stable analog of the transition state structure for the benzoyl ester hydrolysis of chair cocaine 6, 7, 9. In turn, the encouraging experimental results13 support the thrust of these computations.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Such a TSA structure (depicted in Chart ) was synthesized and 85 cocaine esterases out of 450 antianalog antibodies were elicited—a performance markedly superior to that of a previously employed simple phosphonate ester as a stable analog of the transition state structure for the benzoyl ester hydrolysis of chair cocaine 6, 7, 9. In turn, the encouraging experimental results13 support the thrust of these computations.…”
Section: Resultssupporting
confidence: 56%
“…Here we report the computational studies, whereas the corresponding experimental studies have been reported elsewhere (the computational studies described in this report were actually completed far before the experimental studies described in ref. 13, but the submission of this report for publication was delayed consideralby due to some unexpected reason) 13…”
Section: Introductionmentioning
confidence: 99%
“…These studies have used other TSAs, but, so far, the catalytic antibodies produced have had K m values in the millimolar range and/or K cat values well below 1 min −1 [3740]. Attempts to mutate previously identified cocaine catalytic antibodies have not been any more successful [41].…”
Section: Cocaine Catalytic Antibodiesmentioning
confidence: 99%